γδ TCR T lymphoblastic leukemia in a child presenting with marked hyperleukocytosis - Jirong Mass; Bachir Alobeid (Clinical Case Reports, 2021)
Abstract γδ TCR T lymphoblastic leukemia is rare in children and should be differentiated mainly from hepatosplenic T‐cell lymphoma in this age group.